Manajemen Bisnis Syariah dalam Menciptakan Lingkungan Kerja yang Etis dan Produktif - Assegaf, Najwa; Midan; Aida, Nur; Ridho, Muhammad (Al-fiqh, 2025)
This study aims to analyze the role of Islamic business management in creating an ethical and productive work environment. Using a library research approach, this research reviews various literature related to the functions of Islamic management, Islamic principles, and their application in the modern workplace. The findings indicate that the implementation of values such as justice, honesty, transparency, trustworthiness, and social responsibility significantly contributes to improving productivity, employee well-being, and workplace harmony. Islamic business management is not only oriented toward financial profit but also emphasizes spiritual and social dimensions, making it relevant in addressing the challenges of globalization. Therefore, this management model has the potential to serve as a strategic solution for building a sustainable, ethical, and faith-based work system.